PEMETAAN TINGKAT KEBISINGAN YANG DITIMBULKAN OLEH MESIN PENGOLAH KELAPA SAWIT DI PT. TASMA PUJA, KABUPATEN KAMPAR-RIAU - Ade saputra; Defrianto '; Tengku Emrinaldi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The mapping noise levels generated by the palm oil processing machine in PT. Tasma Puja Kab. Kampar, Riau by using grid method has been conducted . The result was the noise intensity of the lowest to the highest one at 121 points in a safe area. The intensity was described in mapping using